1968
DOI: 10.1002/jsfa.2740190701
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of meat freshness in quality control employing chemical techniques: A review

Abstract: Numerous chemical and physical tests have been described which reflect the biochemical and other changes which occur in meat during storage. Although some work has occasionally included the correlation with organoleptic data, there have been few suggestions as to possible critical legal or control limits. In industrial control, however, each method has to be considered in relation to the purpose intended and semi-empirical tests may be of value provided that the procedure is standardised. Critical maxima based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 46 publications
4
30
0
1
Order By: Relevance
“…The results revealed that both control and pediocin NCDC252 with disodium EDTA treated carcasses showed significant increase in TV value as storage period increases. This is in agreement with Pearson (1968), Kandeepan and Biswas (2007) and Chueachuaychoo et al, (2011).…”
Section: Tbasupporting
confidence: 92%
“…The results revealed that both control and pediocin NCDC252 with disodium EDTA treated carcasses showed significant increase in TV value as storage period increases. This is in agreement with Pearson (1968), Kandeepan and Biswas (2007) and Chueachuaychoo et al, (2011).…”
Section: Tbasupporting
confidence: 92%
“…The ideal pH level for meat products is between 5.8 and 6.3 while 6.5 may be considered as an indicative for starting spoilage of meat (Pearson, 1968). At high pH (6.0 or higher) meat will spoil quicker than meat with a pH of (5.3 to 5.7) AMPC, (2002).…”
Section: Chemical Analysis: 321-hydrogen Ion Concentration (Ph)mentioning
confidence: 99%
“…VBN was measured by the modified micro diffusion assay according to the method described by Pearson (1968). Each meat sample (3 g) was homogenized for 1 min with 3 mL distilled water and 6 mL TCA (10%), and then centrifuged at 2,090×g for 15 min.…”
Section: Vbn (Volatile Basic Nitrogen) Evaluationmentioning
confidence: 99%